giải ptrinh
a)(x-1)(5x+3)+(3x-8)(x-1)
b)(x+5)(2x-1)=(2x-3)(x+1)
c)(2-3x)(x+11)=(3x-2)(2-5x)
d)(2x2+1)(4x+3)=(2x2+1)(x-12)
e)(2x-1)2+(2-x)(2x-1)=0
g)(x+2)(3-4x)=x2+4x+4
h)(x-1)(x2+5x-2)-(x3-1)=0
i)x2+(x-2)(11x-7)=4
K)x3+1=x(x+1)
l)x3+x2+x+1=0
m)(x+2)(x2-3x+5)=(x+2) x2
n)2x2-x+3-6x
Mình giải từ cuối lên , mình giải dần -)
n, <=> x(2x-1)-3(2x-1)=0
<=> (x-3)(2x-1)=0
<=> x= 3 hoặc x= 1/2
m, <=> (x+2)(x2-3x+5)-x2(x+2)=0
<=> (x+2)(x2-3x+5-x2)=0
<=> (x+2)(5-3x)=0
=> x= -2 hoặc5/3
trả lời chi tiết giúp mình với